2019
DOI: 10.3390/su11051251
|View full text |Cite
|
Sign up to set email alerts
|

Fusing Sentinel-2 Imagery and ALS Point Clouds for Defining LULC Changes on Reclaimed Areas by Afforestation

Abstract: The study was performed on two former sulphur mines located in Southeast Poland: Jeziórko, where 216.5 ha of afforested area was reclaimed after borehole exploitation and Machów, where 871.7 ha of dump area was reclaimed after open cast strip mining. The areas were characterized by its terrain structure and vegetation cover resulting from the reclamation process. The types of reclamation applied in these areas were forestry in Jeziórko and agroforestry in the Machów post-sulphur mine. The study investigates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…For the LULC classes of broad-leaved forest, coniferous forest, and transitional woodland shrub, we can observe a dynamic change in growth. In previous studies [11][12][13], these areas showed an increase of spatial range in forested areas from the year 2000 to 2016, using image classification of Landsat 7 (2000), on-screen vectorization orthophoto (2009), Landsat 8 (2013), and the image classification of Sentinel-2 (2016).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…For the LULC classes of broad-leaved forest, coniferous forest, and transitional woodland shrub, we can observe a dynamic change in growth. In previous studies [11][12][13], these areas showed an increase of spatial range in forested areas from the year 2000 to 2016, using image classification of Landsat 7 (2000), on-screen vectorization orthophoto (2009), Landsat 8 (2013), and the image classification of Sentinel-2 (2016).…”
Section: Discussionmentioning
confidence: 96%
“…The results of the Sentinel-2 image classification (2016), the LULC classification for the analysed area, are presented in Figure 6. The assessment parameters have the following values: AA = 86.17%, AR = 87.73%, and OA = 90.54% (Table 2) [11,56,57]. The most dominant LULC classes for the Jeziórko area are forested areas.…”
Section: Jeziórko Sulfur Minementioning
confidence: 99%
See 3 more Smart Citations